2022
DOI: 10.1021/acssuschemeng.2c05705
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical In Situ Self-Healing of Porous Nanosheets Based on the Phase Reconstruction of Carbonate Hydroxide to Layered Double Hydroxides with Unsaturated Coordination Metal Sites for High-Performance Water Oxidation

Abstract: The highly oxidized metal sites with unsaturated coordination derived from in situ electrochemical reconstruction combined with the dynamic adaptive surface geometry construction of the catalyst are of the utmost importance to enhance the intrinsic activity of the catalysts for oxygen evolution reaction (OER). Although the dynamic phase reconfiguration of catalysts during the OER process has been widely observed, the reconfigured active phase is only limited to the unitary metallic (oxygen) hydroxides. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…Recently, transition metal-based electroactive materials (such as layered double hydroxides, 14,15 selenides 16,17 and nitrides 18,19 ) have been extensively applied in pseudocapacitors and OER due to their abundant redox active sites and suitable d-band center. 20,21 Among them, NiFe layered double hydroxide (NiFe-LDH) has gained significant attention because of the remarkable synergistic effect between nickel and iron, as well as the interlayer adjustable anions. [22][23][24] What's more, it is widely reported that NiFe-LDH materials follow the LOM during OER and possess a relatively negative redox potential window.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transition metal-based electroactive materials (such as layered double hydroxides, 14,15 selenides 16,17 and nitrides 18,19 ) have been extensively applied in pseudocapacitors and OER due to their abundant redox active sites and suitable d-band center. 20,21 Among them, NiFe layered double hydroxide (NiFe-LDH) has gained significant attention because of the remarkable synergistic effect between nickel and iron, as well as the interlayer adjustable anions. [22][23][24] What's more, it is widely reported that NiFe-LDH materials follow the LOM during OER and possess a relatively negative redox potential window.…”
Section: Introductionmentioning
confidence: 99%
“…32 Metalnitrides were also known to convert into the metal oxyhydroxide due to the surface reconstruction by anodic oxidation during the oxygen evolution reaction. [33][34][35] For instance, Schuhmann and his colleagues demonstrated that in situ generated CoOOH that has been obtained from Co 2 N can speed up the reaction kinetics for the OER. 36 However, due to the absence of oxygen-binding sites, the OER activity of nickel-based electrocatalysts is poor.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the expensive price, paucity of reserves, and poor stability of these precious metal-based electrocatalysts have prevented large-scale commercial applications of the water electrolysis technique. Furthermore, substantial overpotential to trigger the reaction reduces energy conversion efficiency and makes it difficult to use in devices for practical applications. On the other hand, two-dimensional (2D) nanomaterials like graphitic carbon nitride, transition metal oxides, layered double hydroxides, and transition metal dichalcogenides exhibit distinct chemical and physical properties. Their huge lateral size, atomic thickness, large specific surface area, and high surface-to-volume atom ratio make them suitable for a wide range of applications including energy storage, electrocatalysis, electronics, sensors, and so on. These intriguing features and broad uses have also fueled researchers to fabricate 2D metal–organic framework (MOF) nanosheets.…”
Section: Introductionmentioning
confidence: 99%